Faculty Development and Other Strategies for Clinical Teaching - Clare, Camille A.; Yeh, John (Current Women's Health Reviews, 2015)
Bedside teaching is a time honored educational modality for residents and medical students. In this review, we evaluate specific successful strategies for bedside teaching. These strategies are defined, and the evidence for their use is examined. Electronic databases were searched for the period covering the years from 2000 to 2014 for studies in the English language with the main outcome measure of the effectiveness of bedside teaching as an educational tool, reflecting the most current literature. An overall assessment of the optimal techniques for bedside teaching is performed. These include appropriate patient selection, faculty development and education on teaching strategies, and the use of resident preceptors as future ambassadors of bedside teaching. We conclude that this teaching method still has merit for the medical education of students and residents.
Keywords: teaching